Use of Ubuntu Spiritual Psychotherapy in Counselling adolescents with Conduct Disorder in Nkayi Secondary Schools, Zimbabwe - Khumbulani Siziba; Metron Siziba; Sylod Chimhenga (Utan Kayu Publishing, 2024)
The aim of this study was to embrace Ubuntu Spiritual Psychotherapy as a technique for counselling adolescent with conduct disorder in Nkayi Rural District secondary schools. Ubuntu Spiritual Psychotherapy is an approach that combines elements of Ubuntu philosophy, spiritual principles, and psychotherapy to address the psychological and spiritual well-being of individuals. When it comes to counselling adolescents with conduct disorder in secondary schools, it has been observed by the researcher that Ubuntu Spiritual Psychotherapy miss the mark in utilising the valuable approach by failing to take a holistic view of individuals, considering their psychological, emotional, social, and spiritual dimensions. Understanding the cultural background of the adolescents and respecting their beliefs and values is a problem with rural secondary school teachers. The study is guided by Bronfenbrenner’s Ecological Systems theory. The nature of this research was essentially qualitative and phenomenological research design guided data gathering from 20 participants through focus group discussion and individual interviews with students, school counsellors and parents. The study concluded that although most of the teachers in schools appreciate Ubuntu spiritual psychotherapy as a holistic approach to counselling adolescent students with conduct disorder, some barriers such as inadequate knowledge and skill, lack of collaboration and training, negative attitudes and unavailability of standardised protocols condenses its effectiveness. The study further concluded that educators in secondary schools should embark on integrating Ubuntu spiritual psychotherapy into counselling practices in secondary schools to support adolescents with conduct disorders through appropriate teacher training and professional development on Ubuntu spiritual psychotherapy, collaboration between parents, teachers, school counsellors and mental health professionals and establishing a supportive and nurturing classroom environment. This study therefore recommended that teachers and school counsellors need to embrace Ubuntu Spiritual Psychotherapy as a technique for counselling adolescents with conduct disorder in secondary schools, through a collaborative effort from learners, parents, teachers, school counsellors and significant others.